An electrochemical SARS-CoV-2 biosensor inspired by glucose test strip manufacturing processes. Issue 30 (17th March 2021) - Vezza, Vincent J.; Butterworth, Adrian; Lasserre, Perrine; Blair, Ewen O.; MacDonald, Alexander; Hannah, Stuart; Rinaldi, Christopher; Hoskisson, Paul A.; Ward, Andrew C.; Longmuir, Alistair; Setford, Steven; Farmer, Eoghan C. W.; et al.
Abstract : A rapid, low cost sensor for Covid-19 was developed using a perfluorodecanthiol layer and ACE2. Abstract : Accurate and rapid diagnostic tests are critical to reducing the impact of SARS-CoV-2. This study presents early, but promising measurements of SARS-CoV-2 using the ACE2 enzyme as the recognition element to achieve clinically relevant detection. The test provides a scalable route to sensitive, specific, rapid and low cost mass testing.